The national institutes of health's approach to address research gaps in pancreatitis, diabetes and early detection of pancreatic cancer. Issue 5 (September 2021) - Serrano, Jose; Rinaudo, Jo Ann; Srivastava, Sudhir; Ghosh, Sharmistha; Unalp-Arida, Aynur; Andersen, Dana K.
Abstract : Purpose of review: Diseases of the pancreas are a broad spectrum of conditions resulting from metabolic, inflammatory, and neoplastic processes (pancreatitis, pancreatogenic diabetes, and pancreatic cancers). Pancreatic diseases cause significant morbidity, mortality, and cost. Recent findings: Research progress in diseases of the exocrine pancreas (chronic pancreatitis [CP], pancreatogenic diabetes mellitus, and pancreatic cancer) has been hampered by the disorders' heterogeneity, the limitations of previous small cross-sectional studies, the inability to safely obtain pancreatic tissue for study, and the lack of structured epidemiology tools, genetic testing, and biomarker development. Summary: Given the increasing incidence and prevalence of CP and its complications, high mortality rate, and associated healthcare cost, the National Institute of Diabetes and Digestive and Kidney Diseases and the National Cancer Institute funded the Consortium for the study of Chronic Pancreatitis, Diabetes and Pancreatic Cancer (CPDPC) to identify research gaps and foster multidisciplinary collaborations to better diagnose, characterize and manage CP and its sequelae and to understand the diabetes/pancreatic cancer association. The studies undertaken by the CPDPC are described in other articles in this journal's issue.